Semantic-to-autobiographical memory priming causes involuntary autobiographical memory production: The effects of single and multiple prime presentations. - Mace, John H.; Kruchten, Emilee A. (Memory & Cognition, 2023)
A number of studies (Mace et al., Memory & Cognition, 47, 299–312, 2019; Mace & Unlu, Memory & Cognition, 48, 931–941, 2020) have demonstrated that the activation of semantic memories leads to the activation of autobiographical memories on an involuntary memory task (the vigilance task; Schlagman & Kvavilashvili, Memory & Cognition, 36, 920–932, 2008), suggesting that this form of priming (semantic-to-autobiographical) plays a role in the production of involuntary autobiographical memories in everyday life. In the current study, we investigated the effects of prime repetition on involuntary memory production in the vigilance task. Primed participants were either treated to one priming session, where they judged the familiarity of words (e.g., parade), or three priming sessions, where they also judged the familiarity of words as well as decided whether sentences containing the words made sense (e.g., the parade dragged on for hours), and if their corresponding images were sensible (e.g., an image of a parade). The results showed that primed participants produced more involuntary memories with primed content on the vigilance task than control participants, and three-session primed participants produced more memories than one-session primed participants. Similar to other areas where prime repetition has been investigated (e.g., implicit memory, semantic priming), the results show that prime repetition enhances semantic-to-autobiographical memory priming. The results also further support the idea that semantic-to-autobiographical memory priming may play a significant role in the production of involuntary memories in everyday life, as concept repetition is a likely part of everyday experience. These implications, as well as others, are discussed.